Can we use peripheral tissue biopsies to diagnose Parkinson's disease? A review of the literature. (23rd June 2015) - Schneider, S. A.; Boettner, M.; Alexoudi, A.; Zorenkov, D.; Deuschl, G.; Wedel, T.
Abstract : Phosphorylated α‐synuclein (phosαSYN) containing inclusions in neurons (Lewy bodies, LB) and nerve terminals (Lewy neurites, LN), the pathological hallmark of Parkinson's disease (PD), are not confined to the central nervous system, but have also been reported in peripheral tissues. However, the usefulness of αSYN/phosαSYN detection in tissues accessible to biopsies as a reliable biomarker for prodromal PD remains unclear. A systematic review of studies using biopsies of skin, olfactory and gastrointestinal (GI) tissues was conducted to evaluate the sensitivity and specificity of both αSYN and phosαSYN staining in PD patients. Data analysis was hampered by the diversity of the methods used, e.g. choice of biopsy sites, tissue processing, staining protocols and evaluation of the findings. Tissue obtained from GI tract/salivary glands (13 post‐mortem, 13 in vivo studies) yielded the highest overall sensitivity and specificity compared to skin (three post‐mortem, eight in vivo studies) and olfactory mucosa/bulb (six post‐mortem studies, one in vivo study). In contrast to phosαSYN, αSYN was more consistently detectable in peripheral tissues of healthy controls. GI tract/salivary glands appear to be the most promising candidate tissue for peripheral biopsy‐taking. phosαSYN is considered as the marker of choice to delineate pathological aggregates from normal αSYN regularly found in peripheral neural tissues. However, the sensitivity and specificity of phosαSYN are not yet acceptable for using phosαSYN as a reliable peripheral biomarker for PD in clinical routine. Further refinement regarding the interpretation of the peripheral αSYN/phosαSYN burden and the phenotypical definition of peripheral LB/LN is needed to optimize screening methods for prodromal PD.